Analisis Akuntabilitas dan Transparansi dalam Pengelolaan Dana Operasional Sekolah pada Lembaga Pendidikan Berbasis Pesantren - Ainun Khafidhotul; Abdillah Mundir (Kartika: Jurnal Studi Keislaman, 2026)
The management of school operational funds is a crucial element in educational management, as it directly impacts the teaching and learning process, the provision of facilities and infrastructure, and the improvement of the quality of educational services. The success of fund management depends not only on the amount of the budget received, but also on the application of the principles of accountability and transparency at every stage. In response to increasing public demands and the complexity of educational organizations, schools are required to manage their finances openly and accountably. This study aims to examine the process of managing school operational funds, identify the forms of accountability and transparency applied, and analyze the management of operational funds based on these principles at SMK Pesantren Terpadu Ngembeh, Dlanggu, Mojokerto. The research employs a qualitative approach, with data collection techniques including in-depth interviews, observation, and document studies. Key informants include the school principal, the treasurer, and the head of administration. The findings are presented through a description of the reality of student operational fund management at the school, including the challenges in implementing accountability and transparency. This study is also expected to provide practical contributions in the form of strategic recommendations for professional, transparent, and accountable financial governance, as well as theoretical contributions to the development of studies in educational financial management